Pengaruh Tambahan Penghasilan Pegawai (Insentif) Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Selatan - Farah Nur; Hety Budiyanti; Ikhwan Maulana (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to determine the effect of additional employee income (incentives) positively and significantly on employee performance, to determine work motivation positively and significantly on employee performance, and to determine the effect of additional employee income (incentives) and work motivation positively and significantly on employee performance at the investment office and one-stop integrated service prov. South Sulawesi. This research was conducted for 2 months, namely February to April 2024. The sampling technique was carried out using saturated sampling by collecting primary data. The results showed that additional employee income was obtained from Thitung of 7.400> Ttabel 2.052, which is above 5%, work motivation obtained by Thitung 8.501> Ttabel 2.052 which is 5% significant. Meanwhile, in the F test, it is known that the significant value of the additional employee income variable and work motivation on employee performance is Fcount 61.809> Ftable 3.12.